Dental anomalies of a child with incontinentia pigmenti: Case report (Research, Society and Development, 2021)
Incontinentia Pigmenti is a rare multi-system dominant genetic disorder caused by a mutation of the IKBKG/NEMO gene, localized on the X-chromosome, locus Xq28, characterized by dermatological, ocular, neurological, and dental alterations. This case report shows Incontinentia Pigmenti dental findings and emphasizes the importance of the dentist's knowledge about these anomalies so that the patient can be regularly monitored throughout the development of the dentition. Keywords: Child, Incontinentia Pigmenti, Tooth Abnormalities.